Interleukin-17D Promotes Pathogenicity During Infection by Suppressing CD8 T Cell Activity - Lee, Younghee; Clinton, Jelita; Yao, Chengfang; Chang, Seon Hee (Frontiers in Immunology, 2019)
Interleukin 17D (IL-17D) belongs to the IL-17 family of cytokines. While the members of the IL-17 family have been implicated in inflammation and host defense, the function of IL-17D remains unclear. Here, we showed that the lack of IL-17D expression confers protection against Listeria infection. A deficiency in IL-17D also resulted in less weight loss with reduced pathogen burden during influenza A virus infection. During infection, the loss of IL-17D resulted in compromised CD8 T cell activity. CD8 T cell depletion in IL-17D-deficient mice restored the bacterial burden to a level similar to that found in WT mice. Similarly, IL-17D-deficient mice in a RAG-deficient background had no difference in bacterial and viral burden compared to WT mice. IL-17D controlled CD8 T cell activity in part by suppressing the function of dendritic cells. We found that IL-17D from the non-hematopoietic compartment regulates protective immunity during infection. Together, our data led to the identification of IL-17D as a critical cytokine during intracellular bacteria and virus infection that suppresses the activity of CD8 T cells by regulating dendritic cells.